Small cell lung cancer and interstitial pneumonia associated with anti‐transcriptional intermediary factor‐1γ‐positive dermatomyositis - Kato, Toshio (Respirol Case Rep, 2019)
Antibodies to transcriptional intermediary factor‐1γ (TIF‐1γ) are strongly associated with malignancy in patients with dermatomyositis but a relatively low risk for interstitial lung disease. We report the case of a 68‐year‐old female with small cell lung cancer (SCLC) and interstitial pneumonia who was diagnosed first with dermatomyositis positive for serum anti‐TIF‐1γ antibodies. Because interstitial pneumonia co‐existed, she was treated with carboplatin and etoposide without radiotherapy. A significant improvement in skin disease and SCLC was seen in response to chemotherapy. The levels of anti‐TIF‐1γ antibodies were also decreased by chemotherapy. Her interstitial pneumonia was mild with normal pulmonary function and did not change during the observation period. This is the first report of dermatomyositis associated with anti‐TIF‐1γ antibodies co‐existing with interstitial pneumonia and SCLC. Because cases with interstitial pneumonia in cancer‐associated dermatomyositis positive for anti‐TIF‐1γ antibodies are few in number, further studies are necessary to elucidate the clinical features.